(untitled) (Medical Forum Monthly, 2024)
Objectives: To compare the frequency of hypotension (changes in the systolic blood pressure) between unilateral and bilateral spinal anesthesia in adult patients undergoing infraumbilical surgeries. Study Design: randomized control trial study. Place and Duration of Study: This study was conducted at the Department of Anesthesia and Intensive Care, Nishtar Hospital Multan from January 2016 to January 2017. Materials and Methods: Total number of patients divided into two groups by lottery method. Mean and standard deviation was calculated for qualitative variable like age and systolic BP. And for qualitative variables like efficacy and ASA status percentages and frequencies were calculated. stratificaton of data was done to control effect modifier and confounder like age , gender and ASA status. Chi square test was applied to calculate P value. P value less than 0.05 considered as significant. Results: A total number of 60 patients were enrolled in the study and divided into two groups, group A (unilateral block) and group B (bilateral block).In unilateral group eight patients having ASA I and 22 patients of ASA II and in bilateral group 22 patients having ASA I and 21 patients of ASA II. Frequency of hypotension was 8 patients in unilateral group and 15 in bilateral group and remaining patients did not show any change in mean arterial BP in both groups. Conclusion: In this study it was concluded that unilateral spinal anesthesia is more effective in terms ofless hypotension as compare to bilateral spinal anesthesia for adult patients undergoing infraumblical surgeries.